Systematic review of the applications of the Objective Structured Clinical Evaluation -OSCE- in Latin American medical training (Boletín Semillero de Investigación en Familia, 2022)
Introduction: OSCE certifies medical competencies with simulated cases that optimize decision making in real scenarios. Its application in Latin America has been limited. Objective: to analyze the results of ECOE in Latin American medical students based on studies published in the scientific literature. Methods: we applied the identification, screening, selection and inclusion phases of PRISMA guide. A selection protocol was applied in three multidisciplinary databases with 15 search strategies, guaranteeing completeness, reproducibility and methodological quality. Results: 11 studies were systematized, with 1,073 subjects from Chile, Mexico, Argentina and Brazil in whom were evaluated 24 medical competences. There was a high heterogeneity in the design of the clinical cases, the number of stations, duration and areas evaluated. The best performance was reported in the competencies for anamnesis, physical examination, procedural and communicative skills, in the areas of endocrinology and public health. Conclusion: the implementation of the OSCE in medical areas constitutes a curricular and evaluative innovation with low research development in Latin America, which is key for the formulation and design of studies in this field.
Keywords: Competencies; OSCE; Medicine; Review; Latin America.